1995
DOI: 10.1111/j.1549-0831.1995.tb00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Farming Practices and Adherence to an Alternative‐Conventional Agricultural Paradigm1

Abstract: Can a farmer's paradigmatic attitudes predict the actual production system used? Data on actual production practices were collected from a statewide random sample of agricultural producers in Nebraska and used to evaluate the research question. Findings suggest that a relationship does exist between production practices and world view, with specific attitudes related to agricultural production practices. These attitudes are especially salient when it comes to the importance of community in maintaining quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 2 publications
0
23
0
1
Order By: Relevance
“…Others have considered community norms (Rickson Saffigna and Sanders 1999;Blake et al 1997;Saltiel et al 1994) and perceived profitability (Hopkins and Johansson 2004;Soule 2001;Saltiel et al 1994;Lockeretz and Madden 1987). A number of authors have also suggested that there may be a relationship between producer worldview and the farming practices he/ she employs (Allen and Bernhardt 1995;Beus and Dunlap 1990;Buttel and Gillespie 1988;Jacob and Brinkerhoff 1986). Beus and Dunlap's (1991) alternative-conventional agricultural paradigm (ACAP) scale has been used on several occasions to provide a framework for assessing adherence to alternative and conventional agricultural paradigms among groups of farmers.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Others have considered community norms (Rickson Saffigna and Sanders 1999;Blake et al 1997;Saltiel et al 1994) and perceived profitability (Hopkins and Johansson 2004;Soule 2001;Saltiel et al 1994;Lockeretz and Madden 1987). A number of authors have also suggested that there may be a relationship between producer worldview and the farming practices he/ she employs (Allen and Bernhardt 1995;Beus and Dunlap 1990;Buttel and Gillespie 1988;Jacob and Brinkerhoff 1986). Beus and Dunlap's (1991) alternative-conventional agricultural paradigm (ACAP) scale has been used on several occasions to provide a framework for assessing adherence to alternative and conventional agricultural paradigms among groups of farmers.…”
Section: Introductionmentioning
confidence: 92%
“…And Lasley et al (1990) found that support for the idea of lowinput farming did not correlate with employment of practices to reduce chemical inputs. Clearly more research on the nature of these relationships is indicated, both for its contribution to social theory (Jackson-Smith and Buttel 2003) and because of its agricultural policy implications (Chouinard et al 2008;Abaidoo and Dickinson 2002;Allen and Bernhardt 1995;Beus and Dunlap 1993).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Salamon et al (1997) found that families that had adopted ''sustainable'' practices often had strong environmentalist traditions or stewardship perspectives that influenced their adoption decisions. Allen and Bernhardt (1995) observed that farmers who had ''worldviews'' corresponding to an alternative agricultural paradigm were less likely to use synthetic fertilizers and herbicides and more likely to employ conservation practices such as field windbreaks and rotational grazing. In his study of landowner motivations in Indiana, Koontz (2001) found that landowners who did not rely on their land for a substantial portion of their income were much more likely to cite non-monetary benefits of landownership than owners who did.…”
Section: Farming Orientation and Ownership Motivationsmentioning
confidence: 98%
“…The direct linkage of farmers' environmental attitudes to behavior has been widely explored using adoption of A. W. Thompson et al agricultural best management practices (BMPs) as dependent variables (Ervin and Ervin 1982;Lynne et al 1988;Allen and Bernhardt 1995;Henning et al 2004;Prokopy et al 2008;Baumgart-Getz et al 2012). The BMPs explored in the adoption literature include a diverse range of behaviors such as no till systems, integrated pest management, or grassed waterways that address soil, nutrient, landscape, and water management goals (Prokopy et al 2008;USDA 2008).…”
Section: Attitudinal Influence On Behaviormentioning
confidence: 98%